Mapeamento de cultura organizacional em uma Universidade multicampi: estudo de caso da Universidade Federal de São Paulo - Sodre, Lilian Farkas [UNIFESP] (2015)
Culture has been one of the most studied dimensions in the organizational context. However, there are few studies investigating the organizational culture phenomenon in public institutions, especially universities. The objective of this research is to map the organizational culture of the Federal University of São Paulo (Unifesp), that lives the effects of a major expansion that turned into multicampi university. This mapping was carried out by applying the OCP model (Organizational Culture Profile) and interviews with some of the top managers of Unifesp. Cultural mapping aims to contribute to the development of the organization with elements that may provide self-knowledge and strengthening of organizational identity. Through the concept that culture is a set of values shared by a group of people, influencing the course of action and the decisions making by members of the organization, we sought to evaluate among 28 values of the OCP model the ones that were perceived by teachers and administrative staff in Unifesp. These 28 values are organized in seven factors and dimensions. The research was conducted with three hundred ninety-two employees, being one hundred eighty-four teachers and two hundred and eight technicians. Nine managers were interviewed. According to the values that were perceived to be prevalent in the organization, according to participants, Unifesp was classified as the Competitiveness factors and social responsibility, indicating that the culture of Unifesp is influenced by job security, concern for the good reputation and being different from other companies, the emphasis on quality, focus on achievement, innovation, caution about their actions, to be socially responsible and to offer opportunity for professional growth.